Unmasking Autism : Discovering the New Faces of Neurodiversity - Price, Devon (New York : Harmony Books, 2022)
"A deep dive into the spectrum of Autistic experience and the phenomenon of masked Autism, giving individuals the tools to safely uncover their true selves while broadening societys narrow understanding of neurodiversity."--
For every visibly autistic person you meet, there are countless "masked" autistic people who pass as neurotypical. Price provides a deep dive into the spectrum of autistic experience and the phenomenon of masked autism. In doing so he gives individuals the tools to safely uncover their true selves while broadening societys narrow understanding of neurodiversity. -- adapted from jacket and publisher info
Conclusion: Integration.
Keywords: Autistic people -- Social conditions; Autistic people -- Social life and customs; Autism -- Social aspects; Neurodiversity -- Social aspects; Diseases of nervous system and mental disorders